Early Right Ventricular Dysfunction in Highly Selected (Totally Free from Cardiovascular Risk Factors and Other Comorbidities) Human Immunodeficiency Virus Patients: A Pilot Study with Advanced Echocardiography - Deidda, Martino (J Cardiovasc Echogr, 2018)
OBJECTIVE: Human immunodeficiency virus (HIV) infection may also be associated with cardiac dysfunction, thus negatively affecting patients’ morbidity and mortality. This preliminary study aimed at evaluating whether bi-and three-dimensional (3D) strain echocardiographic facilities were able to identify alterations in the right ventricular (RV) function in highly selected – because free from cardiovascular risk factors and other comorbidities – HIV patients. MATERIALS AND METHODS: Eight of these specific HIV patients (age: 32.0 ± 3.6 years; 7 months) treated with highly active antiretroviral therapy (HAART) were enrolled and compared with 8 sex-, age-, and cardiovascular risk profile-matched healthy individuals. All underwent clinical evaluation and transthoracic echocardiography coupled with tissue Doppler, two-dimensional (2D), and 3D speckle tracking imaging to examine their RV function. RESULTS: All standard echocardiographic parameters resulted in the normal range, with no significant differences between HIV and controls. On the contrary, 2D longitudinal strain (16.1% ±1.6% vs. 17.8% ±0.9%, P = 0.02) and Global 3D strain (28.5% ±3.6% vs. 33.5% ±1.9%, P = 0.0002) were reduced in the HIV group. Moreover, Global 3D strain values showed a direct correlation with RV fractional area change values (r = 0.66, P = 0.005). CONCLUSIONS: 2D longitudinal and 3D Global strain can identify an early asymptomatic RV impairment in HIV patients free from other risk factors and comorbidities. These findings seem to imply that also in treated with HAART and well-controlled HIV patients an early asymptomatic systolic RV dysfunction is present, as a distinctive and separated pathological entity compared with classic HIV-related pulmonary arterial hypertension and left ventricular dysfunction. In these patients, RV dysfunction is not revealed by standard echocardiography.